Finite element analysis of cold-formed steel web stiffened channels under compression load - Nurul Amira, Amilruddin (2017)
Cold-formed steels sections have been used in construction and industry. This product is strong, safe, durable and cost effective by saving a lot of construction time. In recent year, complex cold-formed steel section appeared due to improvement of technologies. But, the lack of experts in Malaysia, the uses of cold- formed is still limit on roof truss only. Web stiffeners are used to provide reinforcement of joints web to prevent crippling. The aim of this study is to investigate the buckling behaviour of cold-formed with different shape of web stiffeners channels. Finite element analysis (FEA) using LUSAS of cold-formed steel under compression load will be carried out whereas the buckling analysis and stress-strain behaviour of these specimens will be studied. In this research, three types of size specimens will be provided with are short (600 mm), medium (1500 mm) and slender (2000 mm). Furthermore, three types of web stiffener shapes will be used in this research are C section, Σ section and V section. The pinned ended and fixed ended was assign on the specimen and the finding from this are used to validated finite element result. Based on the result of FEA, the stress-strain relationship and behaviour of cold-formed web stiffened channels has been presented. Besides, the buckling loads and deformed shape of the cold-formed have been illustrated. The studies show that the shape of web stiffeners will affect the strength of ultimate load of cold formed steel.